Maziwa Zaidi / More Milk in Tanzania (Phase 2) - Scoping Study and Market Agent (Agripreneur) Baseline Survey and Women in Livestock Business Baseline Survey (WELBI) - Omore, Amos; Omondi, Immaculate; Rao, E.J.O; Ojango, Julie; Mwendia, Solomon; Ngoteya, Godfrey; Jeremiah, Adolf; Urassa, Neema; Magesho, Walter; Gitau, Jennifer; Poole, Elizabeth; Galiè, Alessandra (2023)
Maziwa Zaidi Phase II (2019-2021) is centred around a catalytic core project titled “Agri-entrepreneurship, technology uptake and inclusive dairy development in Tanzania”. The project aims to catalyze uptake of “proven” dairy technology packages that improve the livelihoods of small holder farmers. It will do so by consolidating previous research to date and translating it into an integrated package of pilot interventions. The pilot interventions will generate the evidence needed to attract public and private development investment to take them to scale.